(3QSGdI GdWjQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GHf SjfG OGYjI hWQh JQaV eQGYJgG EPG LOJ GdESJZfGA s
(3BNQgG (B:s
(3hef GdfGS GdHQCI hef EYJbO ZjQ gPG NSQ hSjYde GdXGdehf Edi eGPG jfbdHhf hGdeLO ddg OGFekG CHOkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B877s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs